Numerical search for time-of-flight focusing conditions and its application to the analysis of TOF mass analyzer schemes - Kambarova, Zh.; Saulebekov, A.; Trubitsyn, A. (Engineering Research Express, 2024)
Amethod of searching for high-order time-of-flight focusing conditions based on data of numerical trajectory analysis of corpuscular-optical systems is presented. The method makes it possible to determine the maximum achievable order of focusing, the value of the independent variable (initial coordinate, initial angle, initial velocity or energy) relative to which the focusing is observed, as well as the spatial position of focus. The method has been tested on model problems. The corpuscular-optical properties of time-of-flight devices with known analytical solutions are investigated, and the uniqueness of their parameters in their class is shown.
Keywords: charged particle optics; corpuscular-optical system; time-of-flight focusing; time-of-flight charged particle mass analyzer; electron mirror